Respuesta :
Answer:
x=0
Step-by-step explanation:
-2*(5x-4)=8-3x
-2x * 5x -2 * -4= 8 -3x
-10x+8=8-3x
-10x+3x+8=8-3x+3x
-10x+3x+8=8-3x+3x
-7x+8=8-3x+3x+8
-7x+8=8
-7x=8-8
-7x=0
x=0
Answer:
x = 0
Step-by-step explanation:
First, distribute
- 2 (5x - 4) = 8 - 3x
-10x + 8 = 8 - 3x
Next, rearrange the terms
-10x + 8 = 8 - 3x
-10x + 8 = -3x + 8
Then, Subtract 8 from both sides of the equation
-10x + 8 = -3x + 8
-10x + 8 - 8 = -3x + 8 -8
Then, simplify (I'm not gonna show how but if you want me to just let me know)
-10x = -3x
Then, add 3x to both sides of the equation
-10x = -3x
-10x + -3x = -3x + 3x
Then, simplify
-7x = 0
Then, divide both sides of the equation by the same term
-7x = 0
-7x/-7 = 0/-7
Finally, simplify
x = 0/-7
and you'll get
x = 0